Modelling and simulation of magnesium antimonide based thermoelectric generator - Md. Nazibul Hasan; Herlina Abdul Rahim; Mohd Ashraf Ahmad; Mohamed Sultan Mohamed Ali (Institute of Advanced Engineering and Science, 2020)
This paper presents the modelling and simulation of a π-shaped Mg3Sb2 based thermoelectric generator. The performance of the proposed thermoelectric generator is evaluated with finite element analysis. A number of thermocouples were varied for high output power and power efficiency factor. Based on the analysis, we demonstrated that enhancement of the temperature gradient and the number of thermocouples are beneficial for high output power and power efficiency factor of Mg3Sb2 based thermoelectric generator. A high output power and power efficiency factor of 8.89 mW and 3.47 mWmm-2K-2 were obtained at a temperature gradient of 500K across the hot and cold side for four Mg3Sb2 based thermocouples, respectively. The obtained results show that the developed device could be used to drive portable electronic devices.